2022
DOI: 10.1021/acsomega.2c03144
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties and Flexibility of Polyacrylonitrile/Graphene Oxide Composite Nanofibers

Abstract: Energy storage and modern electronics industries are in essential need of high dielectric and highly flexible materials. In this study, polyacrylonitrile and reduced graphene oxide (PAN/GO) were prepared by electrospinning. The composite morphology produced a homogeneous, smooth, and flexible surface with high tensile strength and durability. The diameter of the fibers in the composite mats ranged from 232 to 592 nm. The X-ray diffraction pattern recording displayed a sharp peak characteristic centered between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Meanwhile, DSC and TGA assays are conducted for the development and research of pure drug compounds to investigate the stability of novel drug compounds and to investigate polymorphic and purity forms of the drugs . The study on the thermal behavior is usually done as an additional characterization in the development of drug delivery media, for example, hydrogels, , nanoparticles, and nanofibers. , In another research, the DSC test on a hydrogel containing red betel leaf extracts showed a phase transition of the extract from crystalline to an amorphous structure after being encapsulated in a hydrogel . A hydrogel with guava leaf extracts also causes a change in the melting point of the PVA hydrogel to a lower temperature …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, DSC and TGA assays are conducted for the development and research of pure drug compounds to investigate the stability of novel drug compounds and to investigate polymorphic and purity forms of the drugs . The study on the thermal behavior is usually done as an additional characterization in the development of drug delivery media, for example, hydrogels, , nanoparticles, and nanofibers. , In another research, the DSC test on a hydrogel containing red betel leaf extracts showed a phase transition of the extract from crystalline to an amorphous structure after being encapsulated in a hydrogel . A hydrogel with guava leaf extracts also causes a change in the melting point of the PVA hydrogel to a lower temperature …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, according to results in the XRD and XPS data, the presence of oxygen functional groups on the surface of LG nanosheets produces polarization while suppressing the nanocomposite's loss tangent due to their resistive nature. 50,51 Another point, correlated the previous one, explaining excellent dielectric performance for f LG = 0.08, is to consider the evolution of the ratio between the rise in the value of the dielectric constant k and the degradation (i.e. increase) of the dielectric loss ε″ (also the imaginary part of complex dielectric permittivity (ε*), i.e., ε″ = tanδ × k) as f LG increases.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 96%
“…[53] There are other studies conducted to explore dielectric properties of rGO/polymer nanocomposites; however, their reported efficiencies were comparably low. [45,46,[48][49][50][51][52][53][54][55][56]…”
Section: Reduced Graphene Oxide (Rgo)mentioning
confidence: 99%
“…Although they obtained a high dielectric constant of 86.4 at 102 Hz, the dielectric loss has enhanced to 4.97. [ 49 ] Li et al incorporated exfoliated graphene (EG), graphene oxide (GO), and reduced graphene oxide (r‐GO) separately into PVDF through 3,4,9,10‐perylenetetracarboxylic acid ( P y ) to prepare GO/PVDF, rGO/PVDF, P y rGO/PVDF, EG/PVDF, and P y EG/PVDF composites with different filler contents. The P y EG/PVDF showed the highest enhancement of dielectric constant as shown in Figure 4f,g, up to 480 with 0.74 vol% of EG with a comparatively low dielectric loss of 0.27.…”
Section: Polymer 2d Nanocompositesmentioning
confidence: 99%